STRATEGY MODEL KEEP- GRASSROOT SYSTEM FOR IMPLEMENTING MANAGEMENT OF CHANGE: CASE STUDY TRANSFORMATION OF UIN SULTAN AJI MUHAMMAD IDRIS SAMARINDA - Sari, Elly Kartika; Ridwan, Muhtadi; In’am Esha, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: This study investigates the leadership strategies employed in managing institutional transformation at Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda. Purpose: This study explores the change management strategy employed during the transformation of the State Islamic College (STAIN) Samarinda into the State Islamic Institute (IAIN), and ultimately into the State Islamic University (UIN) Sultan Aji Muhammad Idris Samarinda. Method: Employing a qualitative case study approach, data were gathered through in-depth interviews, observations, and documentation, with analysis conducted using NVivo 12 Pro software. Result: The findings reveal that the transformation process was guided by a leadership strategy referred to as the “KEEP-Grassroot System,” which emphasizes four interrelated dimensions: collaboration, enculturation, education, and participation. This strategy enabled leaders to facilitate inclusive decision-making, integrate local wisdom, promote educational values, and foster broad community engagement. The study argues that leadership in change management should not be oriented merely toward control, but rather toward enabling and facilitating institutional adaptation. Conclusion: This case highlights how effective leadership practices rooted in a grassroots approach can strengthen institutional identity, cultural integration, and organizational resilience. The research offers theoretical contributions to organizational change management and provides practical insights for higher education leaders seeking to implement sustainable transformations